The Hindenburg disaster, 1937 - Tarshis, Lauren; Dawson, Scott, 1967- (New York, NY : Scholastic, 2016)
Hugo Ballard is flying on the Hindenburg with his parents, and his sister, but as the zeppelin gets ready to land, a blast rocks the Hindenburg and fire consumes the ship. The entire disaster lasts a mere thirty-two seconds, but in those few seconds, Hugo finds himself separated from his family and in a desperate race to escape the flames. Will he survive this historic disaster?
Includes bibliographical references.
3rd-5th graders.
Grade 4.
700
Accelerated Reader AR
Keywords: Hindenburg (Airship) -- Juvenile fiction; Aircraft accidents -- Juvenile fiction; Airships -- Juvenile fiction; Survival -- Juvenile fiction; Historical fiction